Problem-Based vs Design-Based Learning: Which Better Develops Computational Thinking in Middle School Science Students? - Fadilah, Rizka Elan; Supeno, Supeno; Rusdianto, Rusdianto; Nuha, Ulin; Firdausi, Soraya; Prasetya, Ferry Budi; Izza, Nuril Ayyamil; Khasfiyatin, Siti (Jurnal Pendidikan MIPA, 2024)
Computational thinking has become a crucial skill for students because it gives them the tools to solve complicated issues using organized methods. Implementing Problem-based learning and Design-based learning in science learning has significantly enhanced students' skills. This research aims to ascertain which of the two models is better for facilitating computational thinking skills among middle school students in science learning. The study used a sample of 69 middle school students selected through random sampling. This research employs a quasi-experimental, multi-group, post-test-only design. The instrument utilized in this research is a computational thinking skills test comprising five questions. The data were analyzed using one-way ANOVA to test the hypotheses. Tukey test results indicate that the mean difference score between the PBL and DBL groups is 1.2609, with a significance value greater than 0.05. The study confirms that Problem-based learning is more effective than Design-based learning in facilitating students' computational thinking skills. However, the difference between the two is not particularly noteworthy. PBL and DBL represent viable pedagogical approaches that can enhance middle school students' computational thinking skills in science learning.         Keywords: problem-based learning, design-based learning, computational thinking skill. DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1214-1223